Temporal and spatial variability in hydrography and dissolved oxygen along southwest Nova Scotia using glider observations. (1st February 2023) - Burke, Meredith; Grant, Jon; Filgueira, Ramon; Sheng, Jinyu
Abstract: Dissolved oxygen (DO) in the global ocean is on the decline, resulting in the degradation of coastal habitats. As aquaculture production occurs in these regions, proper understanding of coastal DO dynamics is important for improved farm management (e.g. site selection). The main objective of this study was to quantify along-shore and cross-shore variability in DO dynamics, as well as onshore advection of offshore waters to the bays that could contain aquaculture farms. For that purpose, a Slocum underwater glider was deployed between September 25 and October 12, 2020 to collect high-resolution data of temperature, salinity and DO along a transect between Shelburne Bay and St. Margarets Bay, Nova Scotia, Canada, with an average distance of about 15 km from shore. The observations revealed the variable nature of cross-shore water properties. Shoreward bottom currents transport offshore waters to the coast, and combined with longer residence times, mixing of these waters with those present created a mosaic of differing water properties, with warmer, fresher, and less oxygenated shoreward waters. The glider intercepted an upwelling event due to strong and persistent southwesterly winds, which cooled the upper water layers by 6 °C and increased DO by 1.4 mg L −1 . This strong upwelling event detected at 10 km from the coast was also captured 30 h later within St. Margarets Bay, depicting a potential offshore-inshore interaction. Therefore, bay-wide ecosystems and aquaculture production could be affected by intrusions of offshore waters. Highlights: Strong southwesterly winds persistent for 4 days created coastal upwelling, cooling the upper water layers by 6 °C. An upwelling event detected at 10 km from the coast was also captured 30 h later within a coastal embayment. Cross-shore transects revealed warmer, fresher, and less oxygenated shoreward waters compared to those more offshore.